2016
DOI: 10.1063/1.4941585
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium structures of anisometric, quadrupolar particles confined to a monolayer

Abstract: We investigate the structural properties of a two-dimensional system of ellipsoidal particles carrying a linear quadrupole moment in their center. These particles represent a simple model for a variety of uncharged, non-polar conjugated organic molecules. Using optimization tools based on ideas of evolutionary algorithms, we first examine the ground state structures as we vary the aspect ratio of the particles and the pressure. Interestingly, we find, besides the intuitively expected T-like configurations, a v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…(1) the interaction parameters, as defined, should be inversely proportional to temperature]. As positional order is not accounted for in this theory, the purely orientationally ordered phases analyzed in this paper may be metastable with respect to crystalline or smectic order for small L/B or large interactions, where positionally ordered phases were observed in simulations [17,26,33].…”
Section: A Free Energymentioning
confidence: 99%
See 1 more Smart Citation
“…(1) the interaction parameters, as defined, should be inversely proportional to temperature]. As positional order is not accounted for in this theory, the purely orientationally ordered phases analyzed in this paper may be metastable with respect to crystalline or smectic order for small L/B or large interactions, where positionally ordered phases were observed in simulations [17,26,33].…”
Section: A Free Energymentioning
confidence: 99%
“…Both types of interactions (repulsive and attractive) were considered by Heinemann et al [33], who performed molecular dynamics simulations for ellipses with linear quadrupolar interactions confined to a plane. They found that, for relatively small aspect ratios, a plethora of ground state crystalline structures can exist, and they persist to finite temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The ground states of monolayers of hard ellipsoids interacting through a quadrupole pair-potential were recently found. 23 Apart from the T-like configurations, three more particle orientations were predicted to be stable.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the effect of orientational restriction of ellipsoids on the orientational properties of monolayers was studied. The ground states of monolayers of hard ellipsoids interacting through a quadrupole pair-potential were recently found [23]. Apart from the T-like configurations, three more particle orientations were predicted to be stable.…”
Section: Introductionmentioning
confidence: 99%
“…Anisotropic colloids are an exciting and relevant system due to their primary role in soft matter systems. The possibility of manipulation of their shapes and interaction brings a wide range of applications in the selfassembly of colloidal matter [1][2][3], in microfluidics [4][5][6] and in the design of functional devices such as probes and sensors [7][8][9][10][11]. As a particular class of colloids with anisotropic interaction, we mention magnetic colloids, which are micro-sized building blocks with an embedded magnetic moment with dipolar interaction, i.e., particles composed of a magnetic mono-domain having a typical size ranging from 1 to 150 nm [12].…”
Section: Introductionmentioning
confidence: 99%